2017
DOI: 10.1111/nyas.13453
|View full text |Cite
|
Sign up to set email alerts
|

Exploring spatially varying relationships between children's lead poisoning and environmental factors

Abstract: Children's lead poisoning continues to compromise children's health and development, particularly in the inner cities of the United States. We applied a global Poisson model, a Poisson with random effects model, and a geographically weighted Poisson regression (GWPR) model to deal with the spatial dependence and heterogeneity of the number of children's lead poisoning cases in Syracuse, New York. We used three environmental factors-the building year (i.e., the year of construction) of houses, the town taxable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…The regression relationships at the “average” level and at different quantiles are quite different. Shao et al (2017) concluded that more recently built houses with higher average town taxable values would have lower likelihood of lead poisoning, while the children would have a higher chance of exposure to lead if the surrounding of the house had higher soil lead concentration for the “average” relationship via Poisson models [ 11 ]. In this study, the global quantile models confirmed that influential directions extending to both lower and upper tails.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The regression relationships at the “average” level and at different quantiles are quite different. Shao et al (2017) concluded that more recently built houses with higher average town taxable values would have lower likelihood of lead poisoning, while the children would have a higher chance of exposure to lead if the surrounding of the house had higher soil lead concentration for the “average” relationship via Poisson models [ 11 ]. In this study, the global quantile models confirmed that influential directions extending to both lower and upper tails.…”
Section: Discussionmentioning
confidence: 99%
“…During the last decades the U.S. federal and state governments have devoted considerable efforts for lead hazard screening, mitigation, and control via intervention regulations and education programs. For example, the Lead Hazard Control Program of New York have assisted in reducing lead paint hazards in houses and provided lead inspection for rental properties and homes built before 1978 in the city of Syracuse (NY, USA), [ 11 ]. Although the national surveys and local surveillance data indicate that children’s blood lead level (BLL) (e.g., ≥10 g/dL) has declined over time [ 12 , 13 , 14 , 15 ], the incident of lead poisoning remains relatively high in some inner cities of USA.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…National figures of decreases in elevated BLL, ≥5 µg/dL, (Kennedy et al, 2014;Tsoi et al, 2016) obscure the fact that the spatial distribution of exposure is clustered in low-income areas. Studies have found a number of factors associated with BLL that cluster at the censustract level including: mean age of housing, mean value of housing, median housing income, and proportion of vacant housing (Reissman et al, 2001;Sargent et al, 1997;Shao et al, 2017b;Stewart et al, 2014); more so, individual BLL have been found to be spatially auto-correlated (Berg et al, 2017;Griffith et al, 1998). In other words, measurements of BLL are correlated with each other across space, suggesting that an underlying spatial process is influencing levels of exposure (Shao et al, 2017b).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have found a number of factors associated with BLL that cluster at the censustract level including: mean age of housing, mean value of housing, median housing income, and proportion of vacant housing (Reissman et al, 2001;Sargent et al, 1997;Shao et al, 2017b;Stewart et al, 2014); more so, individual BLL have been found to be spatially auto-correlated (Berg et al, 2017;Griffith et al, 1998). In other words, measurements of BLL are correlated with each other across space, suggesting that an underlying spatial process is influencing levels of exposure (Shao et al, 2017b). This spatial process is not likely to be natural, but instead a function of the built environment (Krieger et al, 2003;Miranda et al, 2002).…”
Section: Introductionmentioning
confidence: 99%